Analysis of Potential Differential Characteristics of Albumin Membranes and Vitelin Membranes Quail Eggs (Cortunix cortunix) Due to Hydrogen Peroxide Fluid - Ummu Hidayati Mardiyah; Didik Rahadi Santoso; Unggul Pundjung Juswono (Natural B, Journal of Health and Environmental Sciences, 2017)
The research of analysis the potential difference characteristic of albumin and vitelline membranes quail egg (Coturnix Coturnix) due to contaminated by hydrogen peroxide (H 2 O 2 ) was conducted to determine the effect of hydrogen peroxide (toxic) against the resistance of a cell. Hydrogen peroxide (H 2 O 2 ) is one group of reactive oxygen species (ROS) that can damage lipids, proteins and nucleic acids because they can diffuseion freely passed by bilayer membrane, so that the hydrogen peroxide concentration needs to be controlled. The resistance of a cell can be determined from changes in the value of the measured membrane potential. The method used in the research applied a microelectrode connected with unity gain differential amplifier and PicoScope. The measurement results show that there is a change the potential difference at the albumin membrane and vitellin membrane of quail egg due to contaminated hydrogen peroxide (H 2 O 2 ). The highest value of the membrane potential difference in the concentration 0 ppm at the albumin membrane is (-144 ± 2 mV) and the vitelline membrane is (-172 ± 3 mV), while the lowest value of the potential difference in the concentration 4000 ppm is (-8 ± 2 mV) at the albumin membrane and (-18 ± 1 mV) at the vitellin membrane.